Frontispiece: Nano Metal‐Organic Framework‐Derived Inorganic Hybrid Nanomaterials: Synthetic Strategies and Applications. Issue 24 (25th April 2017) - Mai, Hien Duy; Rafiq, Khezina; Yoo, Hyojong
Abstract : Nano Metal‐Organic Frameworks Nano‐ (or micro‐scale) metal‐organic frameworks (NMOFs), also known as coordination polymer particles (CPPs), have received much attention because of their structural diversities and tunable properties. Besides the direct use, NMOFs can be alternatively used as sacrificial templates/precursors for the preparation of a wide range of hybrid inorganic nanomaterials in straightforward and controllable manners. For more details, see the Review by H. Yoo et al. onpage 5631 ff.